2020
DOI: 10.1136/bmjhci-2019-100046
|View full text |Cite
|
Sign up to set email alerts
|

Mixed methods protocol for a realist evaluation of electronic personal health records design features and use to support medication adherence (ePHRma)

Abstract: BackgroundNational Health Service policy suggests that increasing usage of electronic personal health records (PHR) by patients will result in cost savings and improved public health. Medication adherence means that patients take their prescribed medication as agreed with their doctors. Some of the claimed benefits of PHRs are decreasing healthcare costs and improving medication adherence and patient outcomes.MethodsThis is a mixed methods convergent study, primarily qualitative. The qualitative and quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…We intend to interview around 30-40 health care practitioners since the “gold standard” for a purposive sample is to achieve theoretical saturation. It is impossible to predict an absolute number for theoretical saturation; however, based on prior experience and published recommendations, we believe these figures are reasonable given our objectives, scope, and methodology [ 32 , 36 , 38 , 39 ].…”
Section: Methodsmentioning
confidence: 84%
“…We intend to interview around 30-40 health care practitioners since the “gold standard” for a purposive sample is to achieve theoretical saturation. It is impossible to predict an absolute number for theoretical saturation; however, based on prior experience and published recommendations, we believe these figures are reasonable given our objectives, scope, and methodology [ 32 , 36 , 38 , 39 ].…”
Section: Methodsmentioning
confidence: 84%
“…Consequently, we adopted the Mukumbang et al (2016) RE model which is placed on a multiple case study approach, as shown in phase 2 of Figure 3, and the model permits a mixed‐method (quantitative and qualitative) approach to collecting and analyzing data (Ebenso et al, 2017; McGaughey et al, 2017). We built upon the methodological insights from prior RE mixed‐method empirical studies (Abildgaard et al, 2019; Andrikopoulou et al, 2020; Ebenso et al, 2017) and used Mukumbang et al (2016) RE model as detailed subsequently, starting with Phase 1—developing the IPT.…”
Section: Methodsmentioning
confidence: 99%
“…The UTAUT states that performance expectancy, effort expectancy, facilitating conditions, and subjective norms have an impact on the intention to use a PHR (Blut et al, 2021). Researchers have enriched those models with other factors, such as e-health literacy (Noblin et al, 2012), anxiety (Cocosila & Archer, 2018), trust (Li et al, 2014), personality traits (Xu et al, 2016), privacy issues (Zhang et al, 2018), and fear appeals (Andrikopoulou et al, 2020;Rogers, 1975).…”
Section: Background Of Phrsmentioning
confidence: 99%
“…Research on PHRs varies and concerns various themes, such as design, functional, technical, and clinical evaluation, and adoption (Andrikopoulou et al, 2020;Cafazzo et al, 2012). The topic of adoption is dominant in the literature on medical informatics and information systems on PHRs (Greenhalgh et al, 2010;Studeny & Coustasse, 2014;Wiljer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%